2008
DOI: 10.1158/1055-9965.epi-08-0630
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Epigenetic Alterations of Familial Pancreatic Cancers

Abstract: Background: Little is known about the genetic and epigenetic changes that contribute to familial pancreatic cancers. The aim of this study was to compare the prevalence of common genetic and epigenetic alterations in sporadic and familial pancreatic ductal adenocarcinomas. Methods: DNA was isolated from the microdissected cancers of 39 patients with familial and 36 patients with sporadic pancreatic adenocarcinoma. KRAS2 mutations were detected by BstN1 digestion and/or cycle sequencing. TP53 and SMAD4 status w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
48
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(57 citation statements)
references
References 50 publications
(50 reference statements)
8
48
0
1
Order By: Relevance
“…In other words, targeting SPARC might enhance drug delivery but also pose an increased risk for metastatic dissemination. In addition, several labs have shown that SPARC expression by tumor cells in human pancreatic adenocarcinoma is a prognostic indicator of better outcome, which is in direct opposition to how SPARC expression by the stromal compartment correlates with survival (Brune et al, 2008;Hong et al, 2008;Sato et al, 2003). However, these studies are consistent with the aforementioned data and show that SPARC inhibits pancreatic tumor cell proliferation (Guweidhi et al, 2005;Sato et al, 2003).…”
Section: Discussionsupporting
confidence: 65%
“…In other words, targeting SPARC might enhance drug delivery but also pose an increased risk for metastatic dissemination. In addition, several labs have shown that SPARC expression by tumor cells in human pancreatic adenocarcinoma is a prognostic indicator of better outcome, which is in direct opposition to how SPARC expression by the stromal compartment correlates with survival (Brune et al, 2008;Hong et al, 2008;Sato et al, 2003). However, these studies are consistent with the aforementioned data and show that SPARC inhibits pancreatic tumor cell proliferation (Guweidhi et al, 2005;Sato et al, 2003).…”
Section: Discussionsupporting
confidence: 65%
“…Sato et al, 2003 reported rarely immunohistochemical labeling in primary pancreatic cancer cells, but detected SPARC in the stromal fibroblasts immediately adjacent to the neoplastic epithelium. In the same way, other authors have shown that the methylation of the SPARC gene occurs in 91% of human infiltrating pancreatic adenocarcinoma, 88% of primary human pancreatic carcinoma xenografts and 94% of human pancreatic cancer cell lines (Brune et al, 2008).…”
Section: Discussionmentioning
confidence: 55%
“…Parm1 [6], Tmem184 [58], HIPK-2 [59], Nptx2 [60,61], Tcf7l2 [62][63][64][65], C2Cd4b [66], Sox4 [67][68][69], and Kiss1r [70][71][72] were revealed for the first time to be expressed at this early stage of E8.5 and E14.5. Hipk2 was co-expressed with glucagon, but not insulin, implicating that it might be associated with β-cell differentiation (Figure 4).…”
Section: Daf1/cd55 Foxq1 Nptx2 and Pga5mentioning
confidence: 85%